World Health Organization Disability Assessment Schedule (WHODAS 2.0): revisão de literatura dos processos de validação em grupos distintos e aferição das propriedades psicométricas da versão brasileira para cegos - SILVEIRA, Laís Sampaio da (2016)
The disability assessment allows a detailed picture of the implications that a health condition has on the day of an individual. The World Health Organization (WHO) developed the World Health Organization Disability Assessment Schedule (WHODAS 2.0) to evaluate health and disability and to infer the impact of these conditions on the individual's functionality. Based on the validation of this instrument have been developed two studies. The first aimed to conduct an updated review of scientific articles that validated the WHODAS 2.0 between 2009 and 2015. From a search of major databases, they found 17 scientific articles WHODAS 2.0 validation. Validations occurred in 16 countries and involved studies with different psychometric properties in healthy adults or any health condition in healthy adults or with any health condition. The second study tested the psychometric properties of the Brazilian version of WHODAS 2.0 for people with blindness. Participated 56 blind, with a mean age of 48.4 (± 13.6) years. The psychometric properties were used: internal consistency, test-retest and inter-rater reliability and criterion validity, which used the WHOQoL. The Brazilian version of WHODAS 2.0 showed adequate internal consistency for most domains (Cronbach’s α≥0,65), good reliability test re-test (CCI≥0,63) and inter-rater (CCI≥0,65), and moderate correlation with their domains WHOQoL of the criteria for validity. Only the domain related to school activities or work showed low internal consistency and no significant correlation with the domains of WHOQoL. The Brazilian version of WHODAS 2.0 is reliable and valid for use in people with blindness.